Evaluation of the learning curve for laparoscopic pancreatoduodenectomy by CUSUM analyses. Cohort study. (August 2020) - Morató, O.; Poves, I.; Burdío, F.; Sánchez-Velázquez, P.; Duran, X.; Grande, L.
Abstract: Introduction: Laparoscopic pancreatoduodenectomy (LPD) remains an extremely demanding surgery. The purpose of this study was to describe the learning curve required for its safe implementation. Methods: Fifty consecutive patients undergoing LPD were retrospectively reviewed. The learning curve was clustered into 4 groups: A, B and C (initial phase, n = 10 each) and D (consolidation phase, n = 20). Cumulative Sum (CUSUM) analysis was applied to operative time, conversion rate and severe postoperative complications. Results: No significant differences were observed among groups and phases concerning specific and general postoperative complications, oncological outcomes or mortality. The conversion rate significantly reduced from 90% (9) in Group A to 40% (4) in Group C (p < 0.01). Operative time was longer in the consolidation phase (median of 506 vs 437 min, p < 0.01). Conversely, hospital stays were shorter during the consolidation phase (8 vs 15 days, p < 0.01). CUSUM analysis identified 20-25cases as being enough to complete the learning curve if operative time and severe complications are analysed, while 40 cases would be needed for considering the conversion rate. Conclusions: The learning curve in LPD can be completed after 20–25 procedures. This information will help to design programmes for introducing new surgeons to this technique. Highlights: Despite the complexity of laparoscopic pancreatoduodenectomy (LPD), learning curve can be obtained after 20–25 cases. CUSUM analysis was used to determine the learning curve in terms of operating time, severe complications and conversion rate. LPD learning curve can be reduced when the surgeon's experience include other complex laparoscopic procedures. Knowledge of these figures allows us to design programs to introduce novel HPB surgeons into LPD.